Hai Sia Seafood: A traditional business’s journey of innovation and digitisation - PAN, Gary (Institutional Knowledge at Singapore Management University, 2022)
Set in May 2021, this case describes the journey of transformation Hai Sia Seafood (Hai Sia), a Singapore-based seafood company, embarked upon five years earlier. Hai Sia, a family business established forty-five years earlier, supplied high quality, fresh, and processed seafood at competitive prices for domestic consumption in Singapore. However, the seafood processing industry in the city-state, including the port, was woefully backward. Hai Sia operated a manual processing plant that was twenty years old, and relied completely on labour intensive work processes, even though digitisation was on the rise in the country and consumers were increasingly migrating online in their buying behaviour. The company faced many challenges such as quota constraints on the number of foreign workers it could hire, inconsistency in quality due to human error, low productivity, and more importantly, the changing profile of its customer base. Hai Sia undertook many steps to transform its operations, including plant renovation and automation, digitisation of work processes, expansion into e-commerce, launch of a consumer brand, and product development for the retail market. The results were promising and the business grew from 1800 tons in 2015 to 2500 tons in 2020. However, the considerable corresponding investments to support these initiatives had adversely impacted the company’s profitability. Ang Junting, the deputy director, knew that if he were to spend more time and resources in modernising the business, the senior management would need to be convinced about the returns that these investments would eventually bring. Moreover, he wondered if going forward, a similar business model that centred on automation, upskilling, training, and consumer retail could be successfully replicated in the neighbouring Southeast Asian economies. Through this case study, students will understand the challenges faced in adopting market innovation and technology in a traditional labour-intensive industry, and appreciate the imperative need for the top management to drive key mindset shifts within the organisation. They will also evaluate the role of data analytics in enabling change and learn how it can be used to efficiently track business activities and financial performance.